The TB-specific CD4+ T cell immune repertoire in both cynomolgus and rhesus macaques largely overlap with humans. Issue 6 (December 2015) - Mothé, Bianca R.; Lindestam Arlehamn, Cecilia S.; Dow, Courtney; Dillon, Myles B.C.; Wiseman, Roger W.; Bohn, Patrick; Karl, Julie; Golden, Nadia A.; Gilpin, Trey; Foreman, Taylor W.; Rodgers, Mark A.; Mehra, Smriti; et al.
Summary: Non-human primate (NHP) models of tuberculosis (TB) immunity and pathogenesis, especially rhesus and cynomolgus macaques, are particularly attractive because of the high similarity of the human and macaque immune systems. However, little is known about the MHC class II epitopes recognized in macaques, thus hindering the establishment of immune correlates of immunopathology and protective vaccination. We characterized immune responses in rhesus macaques vaccinated against and/or infected with Mycobacterium tuberculosis (Mtb), to a panel of antigens currently in human vaccine trials. We defined 54 new immunodominant CD4 + T cell epitopes, and noted that antigens immunodominant in humans are also immunodominant in rhesus macaques, including Rv3875 (ESAT-6) and Rv3874 (CFP10). Pedigree and inferred restriction analysis demonstrated that this phenomenon was not due to common ancestry or inbreeding, but rather presentation by common alleles, as well as, promiscuous binding. Experiments using a second cohort of rhesus macaques demonstrated that a pool of epitopes defined in the previous experiments can be used to detect T cell responses in over 75% of individual monkeys. Additionally, 100% of cynomolgus macaques, irrespective of their latent or active TB status, responded to rhesus and human defined epitope pools. Thus, these findings reveal an unexpected general repertoire overlap between MHC class II epitopes recognized in both species of macaques and in humans, showing that epitope pools defined in humans can also be used to characterize macaque responses, despite differences in species and antigen exposure. The results have general implications for the evaluation of new vaccines and diagnostics in NHPs, and immediate applicability in the setting of macaque models of TB.